YogurBerry / Cassandra Caryn Joseph... [et al.] - Joseph, Cassandra Caryn; Crispen, Malilyne; Nasir, Sheryna; Abdul Halim, Ummu Ammarah; Wan Manan, Wan Nurul Zamariah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, 2008)
The name of our business is YogurBerry. The form of business we're involved in is franchising. We are one of the franchisees of YogurBerry in Kota Kinabalu, Sabah selling yogurt-based products. Our outlet is a take-away type of outlet. YogurBerry is a combination of words yogurt and berry, which comes from the mixture of delicious yogurt ice cream and fresh fruit and nut toppings originated from nature-friendly and healthy concept. YogurBerry yogurt ice cream is the ultimate combination of sourness from yogurt and sweetness from ice cream. The outlet is located at the Phase 2 Ground Floor Atrium of Wisma Merdeka shopping complex. The location is strategic because there is high demand for takeaway food from the people whenever they visit Wisma Merdeka. We plan to start our business on the 1st July 2008. Better market coverage and continuous demand are the two major factors which influenced us to choose this business. Overall, this business will have better ' prospects in the future as there are continuous and demands of healthy food with the premium-class interior concept with low fat and low-calorie products go along perfectly with the new well-being and slow-food concept spread worldwide.